PENCEGAHAN SINDROMA METABOLIK PADATENAGA PENDIDIK MELALUI EDUKASI - Novendy; Hartanto; Naibaho, Elsa Mathica; Anggraini, Jerica (Jurnal Serina Abdimas, 2024)
More than one-third of adults have metabolic syndrome risk factors. The prevalence of metabolic syndrome rises with age, and it is associated with a significant risk of morbidity and mortality due cardiovascular disease. People frequently are unaware of the symptoms of metabolic syndrome and are unconcerned about leading a healthy lifestyle, eating an unbalanced diet, and being physically active in daily life. For the purpose of preventing metabolic syndrome, preventive interventions connected to metabolic syndrome should be proposed. Educators are rarely informed about metabolic syndrome. They are rarely educated on how to manage risk factors for metabolic syndrome. As a result, health education are carried out to promote understanding of metabolic syndrome prevention through adjustments in risk factors and lifestyle. The method applied is metabolic syndrome education. Pretest and posttest findings indicate increased knowledge. This activity had a total of 22 participants. The average pretest score was 81.2, and the average posttest score was 87.7. There was an increase of 8% in pretest to posttest scores. Although there was no significant improvement in knowledge, this activity yielded fairly acceptable results. This could be because the participants in this activity are educators with prior understanding of metabolic syndrome. It is believed that the activities would raise awareness of metabolic syndrome and help to prevent the formation of heart disease in the future.